(untitled) (International Journal of Food and Nutritional Sciences, 2026)
The Mughal Empire (1526–1707) represents one of the most significant phases in Indian history in terms of political consolidation, economic prosperity, and socio-cultural synthesis. This paper examines the socio-economic structure of Mughal India with special emphasis on agrarian relations, revenue administration, trade and commerce, urbanization, social hierarchy, and the condition of various social groups. The study analyzes primary chronicles such as the Ain-i-Akbari and contemporary travel accounts along with modern historiographical interpretations. It argues that the Mughal economy was fundamentally agrarian but deeply integrated with regional and global trade networks. While agricultural expansion and administrative reforms strengthened the empire, structural inequalities and fiscal pressures contributed to socio-economic tensions during the later period. The study contributes to understanding the complexities of Mughal socio-economic organization and its long-term impact on Indian society.